Community Perceptions and Preference on The Condition of Temu Traditional Market Facilities and Infrastructure - Widyastuty, Anak Agung Sagung Alit; Puspoyudo, Anggif (Tibuana, 2025)
The market is a palce where producers and consumers meet to interact in buying and selling daily necessities. This interaction activity certainly requires adequate support for facilities and infrastructure. The traditional market of Temu Market located in Sidoarjo Regency is managed by the government with an operational system by the Sidoarjo Regency Market Service. The purpose of this study was to determine the condition of the facilities and infrastructure of the Temu Traditional Market, to determine the perception and preferences of the community towards the facilities and infrastructure of the traditional market and the development strategy of the temu Traditional market based on community perseptions and preferences. The data analysis method used is the analysis of interest performance analysis (IPA). The results of the analysis of the condition of the facilities and infrastructure of the temu Traditional market, out of 13 indicators there are 10 facilities and infrastructure that are appropriate, namely Shops, kiosks, stalls, parking areas, loading and unloading areas, management offices, toilets, places of worship, drainage, trash cans, road access and clean water. The results of the analysis of community perceptions and preferences regarding the Temu Market are the main priorities that need attention are the security post and waste management. The performance that needs to be maintained because it has received good appreciation from the community is the toilet/bathroom, loading and unloading area, management office and place of worship.